Leveraging agricultural revitalisation for peace: Post-conflict recovery, agri-food systems, and food security in Syria - Schapendonk, Frans; Rabie, Sara; Jaskolski, Martina (2025)
Syria’s embattled new government faces a catalogue of competing short-, medium-, and long-term recovery priorities. Agriculture remains, despite extensive damage to agricultural lands and irrigation infrastructure, the backbone of Syria’s rural economy. Its critical pre-war contribution to domestic food security, employment, and Syria’s export economy means a reconstituted agricultural sector has the potential to become an important engine for broader post-conflict recovery. Agricultural reconstruction and recovery strategies must, however, encompass more than just the reconstruction of physical infrastructure, increasing productivity, or the generation of employment opportunities. Critical and likely more thornier issues such as land tenure, returnee (re)integration, equitable natural resource access and management, and the effective dissemination of climate-smart and resilient technologies for adaptation are equally essential undertakings if the sector’s recovery is to be sustainable in the long-term.